Health Correlates of Intimate Partner Violence and Help-seeking Among Unauthorized Immigrant Women - Shuman, Sara (Journal of interpersonal violence, 2022)
Intimate partner violence (IPV) research on immigrant women who are unauthorized is particularly scarce, despite unique vulnerabilities associated with their documentation status that may impact help-seeking and health outcomes. The purpose of this study was to document the frequency of lifetime IPV and related help-seeking behaviors, and examine the relationship between IPV, major depressive disorder (MDD), post-traumatic stress disorder (PTSD), and health-related quality of life (HRQL) among a community health center-based sample of unauthorized, Spanish-speaking immigrant women in Philadelphia. A clinic-based sample of unauthorized Spanish-speaking women (N = 200, ages 18-65) completed an anonymous, cross-sectional survey on IPV experiences, help-seeking behaviors, and self-reported health in 2013-2014. Chi-square tests assessed associations between sociodemographic variables and IPV. Multivariable logistic regression investigated whether IPV predicted mental health outcomes. Approximately one in three (34.5%) women reported lifetime IPV experiences. Of these, half (56.6%) sought help (formal n = 22; informal n = 25) because of the violence. Women identified not knowing where to go, believing that help was not necessary, and embarrassment as barriers to help-seeking. Symptoms consistent with MDD and PTSD were reported by 40.5% and 16% of the sample, respectively. In unadjusted logistic regression models, IPV survivors were more likely to endorse MDD and PTSD, and report low mental health HRQL scores than counterparts without IPV. In fully adjusted models, only the association between IPV and PTSD remained significant (OR: 3.80, p =.01). Study findings document high frequencies of IPV, MDD, and PTSD among this clinic-based sample of unauthorized immigrant women. Women who reported IPV also had a greater likelihood of reporting symptoms consistent with PTSD. Findings highlight the need for clinic-based mental health and trauma-informed services tailored to unauthorized immigrant women as well as interventions to decrease IPV.